Sosialisasi Isi Piringku : Upaya Pencegahan Stunting Pada Balita dengan Pemanfaatan Daun Kelor - Robawa, Rizki Setyo Putro; Aisah Putri Maharani; Fira Fatma Salsabila; Puspita Dwi Firnanda; Intan Permatasari Fitri Agustine; Putri Amabel Carissa Pradana; Condro Widodo (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The problem of stunting among toddlers in Indonesia is still a big challenge that needs to be addressed immediately. The condition of stunting, which occurs due to a lack of nutritional intake in the womb and a lack of public knowledge about good child rearing patterns, has the potential to disrupt children's physical and cognitive development in the long term. This community service program is carried out with the aim of preventing stunting in toddlers through the socialization of